A multicenter phase 2 trial of camrelizumab plus famitinib for women with recurrent or metastatic cervical squamous cell carcinoma - Lingfang Xia; Qi Zhou; Yunong Gao; Wenjing Hu; Ge Lou; Hong Sun; Jianqing Zhu; Jin Shu; Xianfeng Zhou; Rong Sun; Xiaohua Wu (Nature Communications, 2022)
Patients with recurrent or metastatic cervical cancer have limited therapeutic options. Here the authors report efficacy and safety of camrelizumab (anti-PD-1 antibody) in combination with famitinib (anti-angiogenic agent) in pre-treated recurrent or metastatic squamous cervical cancer.